(untitled) - Davis, Jason (New York, NY, 2006)
Effective Academic Writing presents the writing modes and rhetorical devices students need to succeed in an academic setting.
Keywords: English language,Essay,Report writing; Rhetoric,Problems, exercises, etc.,Authorship,Problems, exercises, etc.,Problems, exercises, etc